Woman Work Participation in Yogyakarta Insights from a Comprehensive Study - Hadioetomo Hadioetomo; Joko Susanto; Agus Santosa (Universitas Muhammadiyah Sidoarjo, 2025)
General background: Women’s participation in the labor market has long been recognized as a critical driver of household welfare and national economic growth, yet disparities persist across regions. Specific background: In Indonesia, particularly the Special Region of Yogyakarta, women’s labor force participation remains considerably lower than men’s, reflecting enduring socio-cultural constraints. Knowledge gap: Despite growing research on gender and employment, limited attention has been given to how intersecting factors of household roles, education, and social norms shape women’s labor choices in this region. Aims: This study investigates the determinants of women’s labor market engagement using data from the National Socio-Economic Survey (Susenas), focusing on individual and household characteristics. Results: Findings reveal that only 38.5% of women participate in the labor force compared to 54.8% of men, with a gap of 16.3%. Marital status, childcare and eldercare responsibilities, educational attainment, and discriminatory practices substantially influence women’s employment decisions. Novelty: Unlike prior studies, this research highlights the dual burden of childcare and eldercare as critical, often overlooked barriers limiting women’s opportunities. Implications: The results underscore the need for targeted policies addressing structural and cultural obstacles, thereby fostering gender equality, enhancing household resilience, and supporting sustainable economic development. Highlights: Women’s labor participation in Yogyakarta remains significantly lower than men’s. Caregiving roles for children and elderly strongly limit women’s employment. Policies are needed to address socio-cultural and structural barriers. Keywords: Gender Equality, Labor Force Participation, Household Well-Being, Social Norms, Care Responsibilities